Heard on the Birdline, December 15, 1996-March 15, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Summary of the Iowa Birdline update for December 15, 1996-March 15, 1997. Highlights of the update include early winter sightings of an immature Pinyon Jay and a Clark's Nutcracker. Interesting observations from the Christmas Bird Count were sightings of a gray phase Gyrfalcon and a Pine Grosbeak. Also of note were the late winter sightings of Great Gray Owls, a Ferruginous Hawk, and a Townsend's Solitaire. Epson - sheet feed